Extracranial arteriovenous malformations: a 10-year experience at a German vascular anomaly center and evaluation of diagnostic imaging for endovascular therapy assessment - Werba, Nadja; Ludwig, Johannes; Weiss, Christel; Struebing, Felix; Schoenberg, Stefan; Sadick, Maliha (Frontiers in Medicine, 2024)
Background: Arteriovenous malformations (AVMs) account for less than 3% of vascular anomalies. The aim of this study is to present a 10-year-experience of a German vascular anomaly center (VAC) with AVMs and to evaluate diagnostic imaging for treatment-relevant information for minimally invasive therapy planning. Material and Methods: A retrospective study including patients from the VAC database with AVMs was conducted. Clinical information from patients’ record were evaluated. An additional image reading analysis of the available diagnostic imaging using a 4-point Likert scale, focusing on relevant points for minimally invasive treatment planning, was conducted in 13 patients who had all three magnetic resonance tomography (MRI), computed tomography (CT), and conventional angiography available. Results: Between April 2014 and March 2024, 60 patients (60% female, 40% male; 12% Parkes Weber syndrome) with AVMs presented to the VAC. The median age was 36 years (range: 11-78 years). Referral diagnosis was correct in 73.3% of cases. The mean distance to the VAC was 102.5 kilometers (111.0). The most common locations involved the hand (32%), lower extremity (22%), and pelvis (22%). The most common symptoms were pain (81%), pulsation (64%), and local hyperthermia (62%). Necrosis was significantly more common when the AVM was located in the hand (p = 0.0129), and growth when located in the pelvis (p = 0.0037). Also, cosmetic issues were significantly more frequent when the AVM was located in the head area (p = 0.0333). Most patients presented with Schobinger stage II (57%). Right heart strain was only documented in 1 case. 47% had undergone invasive therapies before VAC admission. In 30% further minimally invasive or invasive therapy was required. In the diagnostic imaging evaluation conventional angiography had the overall best ratings for image quality (median = 1.00; range: 1.00-2.00), nidus evaluation (median = 1.00; range: 1.00-2.00), and therapy planning (median = 1.00; range: 1.00-1.33). Conclusion: Our 10-year-experience showed that in patients with AVMs, the correct diagnosis is often made before admission to a specialized VAC. Diagnostic imaging is essential for endovascular treatment planning, with conventional angiography showing superior utility in image quality, nidus evaluation, and therapy planning compared to other modalities.